Rural Scholars or Bright Rednecks? Aspirations for a Sense of Place Among Rural Youth in Appalachia - Craig B. Howley; Hobart L. Harmon; Gregory D. Leopold (Journal of Research in Rural Education, 1996)
In this article, we promote sense ofplace as a legitimate aspiration ofrural youth, including very able rural youth. The aspiration concerns the quest for rootedness and community as opposed to mobility and individual status. We conducted exploratory analyses ofdata gatheredfrom 158 participants in the 1994 West Virginia Governor's Honors Academy (GHA) andfrom a contrasting group of644 students in seven rural high schools. Findings suggest that GHA students (whether rural or more urban): (I) are less alienated than students in the contrast group; (2) that they are not more eager to leave their local community than students in the contrast group; and (3) that GHA students exhibit stronger modem dispositions than students in the contrast group, but do not exhibit weaker rustic dispositions. In addition, GHA students do not pppear to be less satisfied with their (more urbanized) communities than rural students-at-large; however, rural GHA students do appear to be less satisfied with their local communities than GHA students living elsewhere. Findings are discussed in light ofconventional wisdom about aspirations and in view ofemerging rural s~hool improvement aims